Numerical investigation of the resonance behavior of flow‐excited Helmholtz resonators. Issue 1 (8th October 2019) - Weitz, Michael; Schoder, Stefan; Kaltenbacher, Manfred
Abstract: Functional gaps of cars combined with the underlying volume of air represent Helmholtz resonators that are excited at the Helmholtz frequency by the turbulent flow. Based on a model that describes the spatial coherence of pressure fluctuations beneath a turbulent boundary layer, we present how to compute an extensive synthetic excitation signal without performing computational fluid dynamics (CFD) computations. Moreover, this contribution shows the capabilities of complex fluid models to better predict the resonance behavior of Helmholtz resonators.